Identifying Asymmetric Effects of Labor Market Reforms - Enzo Weber; Britta Gehrke (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper proposes a novel approach to identify structural long-term driving forces of the labor market and their state dependent effects. Based on search and matching theory, our empirical model extracts these driving forces within an unobserved components approach. We relate changes in the labor market structures to reforms that enhance the flexibility of the labor market in expansion and recession. Results for Germany and Spain show that labor market reforms have substantially weaker beneficial effects in the short-run when implemented in recessions. From a policy perspective, these results highlight the costs of introducing reforms in recessions.
Keywords: C32; E02; E32; J08; 330; labor market reforms; search and matching; business cycle asymmetries; Markov switching